Reinvigorate, operationalize! Building new planners and policy makers :Powerpoint - Verplanke, J.J. (University of Twente, 2020)
This lecture presents: The importance of information; The city we need is; Policy benefits from good data; Good Data requires capacity; Capacity development; Reinvigorate; Operationalize.